La conversión al islam como estrategia de cambio y diferenciación en la modernidad (2015)
ABSTRACT: This article seeks to contribute to the knowledge of Islam in the Colombian context, through ethnographic observations and narratives of individuals who have converted to said religion in Bogota. In addition to analyzing the motives for their conversion, it studies the way these people have constructed a new religious identity altering their perception of themselves, their system of beliefs and values, their behavior and their relation to the socio-cultural environment around them. It also examines the link between the private and the public spheres, between the symbolic and the political, that becomes visible when, by openly adhering to a religion that is usually stigmatized, a person resists the hegemonic forms of socialization in Colombian society.